2021
DOI: 10.3390/atmos12081006
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality in the Italian Northwestern Alps during Year 2020: Assessment of the COVID-19 «Lockdown Effect» from Multi-Technique Observations and Models

Abstract: The effect of COVID-19 confinement regulations on air quality in the northwestern Alps is assessed here based on measurements at five valley sites in different environmental contexts. Surface concentrations of nitrogen oxides (NO and NO2), ozone (O3), particulate matter (PM2.5 and PM10), together with a thorough microphysical (size), chemical, and optical (light absorption) aerosol characterisation, complemented by observations along the vertical column are considered. Even in the relatively pristine environme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 74 publications
(94 reference statements)
1
8
0
Order By: Relevance
“…In particular, employing a 1064-nm laser beam can raise possible concerns about the ALC efficiency in detecting fine mode particles, which are especially dominant in case study A. However, the reliability of the ALC in this situation can be justified by the following arguments: (a) as also stated in Section 2.3, other studies (Dionisi et al 2018;Barragan et al 2020;Diémoz et al 2021) have successfully employed such an instrument in similar contexts, showing good agreement with independent data sources;…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In particular, employing a 1064-nm laser beam can raise possible concerns about the ALC efficiency in detecting fine mode particles, which are especially dominant in case study A. However, the reliability of the ALC in this situation can be justified by the following arguments: (a) as also stated in Section 2.3, other studies (Dionisi et al 2018;Barragan et al 2020;Diémoz et al 2021) have successfully employed such an instrument in similar contexts, showing good agreement with independent data sources;…”
Section: Discussionmentioning
confidence: 95%
“…These issues are analysed in more depth in Section 3.4. Previous studies (Dionisi et al 2018;Barragan et al 2020;Diémoz et al 2021), by the way, have already demonstrated the efficacy of this technique, by comparing its retrievals to independent observations from other instruments (such as sky radiometers or research lidars).…”
Section: Automated Lidar Ceilometermentioning
confidence: 98%
See 1 more Smart Citation
“…The procedure illustrated in the present work reveals promising in elucidating the changes in the air pollutant levels that are not easily identifiable in the original data and in identifying an atmospheric response after an intervention or an unplanned event [3]. Finally, it is expected that the proposed procedure can also be worthwhile applied to assess the atmospheric response to social and anthropic activities lockdown established in Italy in the first part of 2020 to fight the spreading of the coronavirus disease (COVID-19) [27,28].…”
Section: Introductionmentioning
confidence: 86%
“…This area is an ideal scenario for investigating how the orography impacts the development of pollution events: mechanically and thermally driven winds, Foehn and temperature inversions are frequent. In particular, plain-valley circulations strongly influence the long-term atmospheric composition [15,16] and can trigger severe pollution episodes [17].…”
Section: Introductionmentioning
confidence: 99%